STUDI KASUS: EFFLEURAGE MASSAGE UNTUK MENURUNKAN INTENSITAS NYERI PERSALINAN - Laisouw, Meilany; Malawat, Ratna (Jurnal Kebidanan, 2023)
Childbirth is the process in which the baby, placenta, and amniotic sac exit the mother's uterus. One of the causes of childbirth is the presence of uterine contractions that produce pain and are very distressing for the delivering mother. Unaddressed pain can affect the mother's health, impacting both the fetus and the childbirth process itself. Various interventions are often provided to laboring mothers to reduce childbirth pain, both pharmacological and non-pharmacological. This case study illustrates the application of effleurage massage on Mrs. A, 25 years old, G2P1A0 in the active phase of the first stage of labor. Effleurage massage induces a relaxation effect, assisting the mother in adapting to the pain and expediting the childbirth process. Healthcare professionals should implement non-pharmacological methods to address childbirth pain, ensuring a swift and safe labor process.